Prognostic impact of incident left ventricular systolic dysfunction after myocardial infarction - Yoshioka, Goro; Tanaka, Atsushi; Watanabe, Nozomi; Nishihira, Kensaku; Natsuaki, Masahiro; Kawaguchi, Atsushi; Shibata, Yoshisato; Node, Koichi (Frontiers in Cardiovascular Medicine, 2022)
Introduction: We sought to investigate the prognostic impact of incident left ventricular (LV) systolic dysfunction at the chronic phase of acute myocardial infarction (AMI). Materials and methods: Among 2,266 consecutive patients admitted for AMI, 1,330 patients with LV ejection fraction (LVEF) ≥40% during hospitalization who had LVEF data at 6 months after AMI were analyzed. Patients were divided into three subgroups based on LVEF at 6 months: reduced-LVEF (<40%), mid-range-LVEF (≥40% and <50%) and preserved-LVEF (≥50%). Occurrence of a composite of hospitalization for heart failure or cardiovascular death after 6 months of AMI was the primary endpoint. The prognostic impact of LVEF at 6 months was assessed with a multivariate-adjusted Cox model. Results: Overall, the mean patient age was 67.5±11.9 years, and LVEF during initial hospitalization was 59.4±9.1%. The median (interquartile range) duration of follow-up was 3.0 (1.5–4.8) years, and the primary endpoint occurred in 35/1330 (2.6%) patients (13/69 [18.8%] in the reduced-LVEF, 9/265 [3.4%] in the mid-range-LVEF, and 13/996 [1.3%] in the preserved-LVEF category). The adjusted hazard ratio for the primary endpoint in the reduced-LVEF vs. mid-range-LVEF category and in the reduced-LVEF vs. preserved-LVEF category was 4.71 (95% confidence interval [CI], 1.83 to 12.13; p<0.001) and 14.37 (95% CI, 5.38 to 38.36; p<0.001), respectively. Conclusions: Incident LV systolic dysfunction at the chronic phase after AMI was significantly associated with long-term adverse outcomes. Even in AMI survivors without LV systolic dysfunction at the time of AMI, post-AMI reassessment and careful monitoring of LVEF are required to identify patients at risk.